Alexander ve oyuncak fare - Lionni, Leo, 1910-1999.; Atakay, Kemal (Ankara : Elma Çocuk, 2019)
Alexander, the mouse, makes friends with Willy, a toy mouse, and wants to be just like him until he discovers that Willy is to be thrown away.
K-3
Caldecott Medal/Honor.
Keywords: Mice -- Fiction; Toys -- Fiction; Mice -- Fiction; Toys -- Fiction